Effect of sex, age and anthropometric measurements on left ventricular mass index in a sample of Iraqi adults. - Mawada M. Funjan; May F. Estephan; Kadem M AL-Hemiary (مجلة كلية الطب, 2011)
Background: Echocardiography is a very important diagnostic modality in the clinical practice of cardiology. Although it has been extensively used as a diagnostic tool. Echocardiography has recently emerged as a sensitive, non invasive technique for evaluating left ventricular mass(LVM) and detecting left ventricular hypertrophy. Objective: to determine the effect of sex, age, and anthropometric measurements on echocardiographic values for cardiac chambers, left ventricular mass index in adults Iraqi sample. Methods: This was observational study based on a randomly selected sample from Baghdad city, 75 normal obese Iraqi subjects with no history of cardiovascular disease underwent transthoracic echocardiography. The following M-mode echocardiographic parameters were measured such as ventricular diameters, interventricular septal thickness (IVSTD), posterior wall thickness in diastole (PWTD), left ventricular mass, left ventricular mass indexes values were expressed as mean and standard error. Results: Echocardiographic values were slightly influenced by gender and age. The overall, cardiac measurements were higher in male gender. LV posterior wall thickness, mass indexes corrected for height2.7 and body surface area (BSA) were influenced by age. In multiple regression analysis age and BSA were a powerful predictors for non indexed LVM or for LVM to BSA , where as body mass index was the strongest predictor of LVM to height 2.7 ( LVM/h 2.7 ). Conclusions: Left ventricular mass (LVM) in normal obese Iraqi adults is age and body surface area (BSA) dependent. Age and body mass index (BMI) were the best predictors of LVM/h 2.7 in normal obese Iraqi adults. Left ventricular mass is larger in men, corrected or not for anthropometric variables.